PENGARUH MODAL, TENAGA KERJA, LAMA USAHA, INOVASI, DAN TEKNOLOGI TERHADAP PRODUKSI INDUSTRI PERHIASAN DI KABUPATEN BADUNG - Kusuma Putra Astawa, Pande Bagus Dharma; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024, 2024)
Production is a very important thing in an industry, so it requires continuous planning and monitoring. Taking into account the factors that have an influence on production will provide convenience in running an industry. The purpose of this study was to analyze effect of capital, labor, length of business, innovation, and technology for the production of the jewelry industry in Badung Regency. This study uses primary data with a quantitative approach obtained from interviews. The population in this study totaled 47 units of the jewelry industry using the entire population as a sample. The sample collection method used is saturated samples. Data analysis techniques using descriptive analysis, multiple regression analysis, and analysis of the coefficient of determination. The results of this study indicate 1) capital, labor, length of business, innovation, and technology simultaneously have a significant effect on the production of the jewelry industry in Badung Regency. 2) capital, labor, length of business, innovation, and technology have a positive and significant effect on the production of the jewelry industry in Badung Regency. 3) capital is a variable that has a dominant influence on the production of the jewelry industry in Badung Regency.